USER’S PERCEPTION ON THE ADOPTION OF COMPUTER-ASSISTED AUDIT TOOLS AND TECHNIQUES (CAATTS) IN DETECTING FRAUD AMONG DEPOSIT MONEY BANKS - ADEYANJU, OLANREWAJU DAVID; ADENIKINJU, OLAYINKA (Innovare Journal of Social Sciences, 2022)
Innovations in information technology have increased the demand for computer-assisted approaches in carrying out audit functions in organizations. In the banking industry, the use of computer-assisted audit tools and techniques (CAATTs) by auditors in combating fraud has become necessary, in the face of emerging challenges. Therefore, this study seeks to assess perceptions on the adoption of CAATTs in fraud detection among deposit money banks (DMBs) in Nigeria. A structured questionnaire on the study variables was developed and a research survey approach was used to harvest information from auditors and audit managers in 20-listed DMBs and the big-four audit firms in Nigeria. One hundred and ninety-nine copies of the questionnaire were properly filled and the data were analyzed using frequency tables, histogram, bar-chart, and the Kruskal–Wallis test, all with the aid of the Statistical Package for the Social Science. The result of the analysis revealed a moderate adoption of CAATTs among the banks. Further results indicated that the educational level of auditor is a major social-demographic variable influencing adoption of CAATTs. The study concludes that educational exposure is a determining factor in the adoption of CAATTs for fraud detection among banks in Nigeria. The study recommends that policymakers and practitioners in the banking sector should include CAATTs into present auditing practices and future laws.